Acupoint catgut embedding alleviates experimental autoimmune encephalomyelitis by modulating neuroinflammation and potentially inhibiting glia activation through JNK and ERK pathways - Liu, Xiaofang; Yang, Liansheng; Su, Zhumin; Ma, Xueying; Liu, Yingying; Ma, Lili; Ma, Xiaomeng; Ma, Mingxia; Liu, Xiaoyun; Zhang, Kun; Chen, Xiaohong (Frontiers in Neuroscience, 2025)
BackgroundAcupoint catgut embedding (ACE) is a traditional Chinese medicine technique commonly used for managing various disorders, including chronic inflammatory pain and allergic asthma. Despite its growing use, the neuroimmunological mechanisms underlying ACE treatment effects remain unclear.MethodsThis study investigated the roles and potential mechanisms of the effects of ACE in treating experimental autoimmune encephalomyelitis (EAE), a frequently used animal model of autoimmune neuroinflammation. The effects of ACE treatment were evaluated by monitoring body weight and EAE severity scores. Behavioral tests, histopathological analysis, ELISA, and flow cytometry were conducted to assess the therapeutic efficacy of ACE. RNA sequencing was performed to uncover ACE-associated transcriptional signatures in the spinal cords of EAE mice.ResultsThe results were validated through western blotting, qRT-PCR, and immunofluorescence (IF) staining. In ACE-treated mice, EAE disease severity was significantly ameliorated, along with improvements in anxiety-like behaviors and reduced inflammation and demyelination. The ACE treatment restored immune imbalance in the EAE mice by decreasing Th17 and Th1 cells, while increasing Treg cells in peripheral immune organs and reducing serum inflammatory cytokine levels. RNA sequencing revealed significant suppression of the genes and pathways associated with reactive microglial and astrocytic activation, corroborated by IF studies. Additionally, ACE treatment could suppress the ERK and JNK signaling pathways at both RNA and protein levels.ConclusionThese findings confirm the protective role of ACE in mitigating EAE symptoms by modulating microglial and astrocytic activity and regulating inflammatory cytokines.